Efek Granul Ekstrak Bawang Daun (Allium fistulosum L.) terhadap Mortalitas Larva Aedes aegypti L. - Resitarani, Elisabeth Dea; Haryati, Sri; Wicaksono, Bagus (Nexus Biomedika, 2014)
Background: Spring onion (Allium fistulosum L.) are known to contain saponin, tanin and flavonoid having larvicide effect. The purpose of this research is to know the effect of granules of spring onion extract (Allium fistulosum L.) on the Mortality of Aedes aegypti L. Larvae. Methods: This research was a laboratory experimental with the post test only controlled group design, which was done at âBalai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatigaâ, Central Java. The subject used in this research was third stage of Aedes aegypti L. larvae. Subjects were taken with incidental sampling technique. The numbers of the subjects were 175 larvae, divided into 7 groups, so each group contained 25 larvae. This treatment was repeated 4 times. Â For the control group it was used 100 ml of water. The other six groups used granules solution of spring onion extract, that were 1,400 mg, 1,700 mg, 2,000 mg, 2,300 mg, 2,600 mg, and 2,900 mg per 100 ml of water. The observation was held after 24 hours then the number of dead larvae was counted. The data were analyzed using One Way ANOVA followed by LSD Post Hoc. Lethal Concentration (LC) value was determined using Probit analysis. Results: There were significant difference of larvicide effect caused by granules of spring onion extract treatment (p = 0.000). The number of dead larvae increased along with the increase in the concentration of granules. LSD test indicated that there was significant difference between two groups except between groups 2,600 mg/100 ml and 2,900 mg/100 ml. The results of probit analysis showed that LC50 was 1,620.55 mg/100 ml and LC99 was 3,333.89 mg/100 ml. Conclusion: The granules of spring onion (Allium fistulosum L.) extract can cause death of Aedes aegypti L. larvae with LC50 in level of 1,620.55 mg/100 ml and LC99 in level of 3,333.89 mg/100 ml. Keywords: spring onion extract, granules, Aedes aegypti L. larvaeÂ